Generalized Forms of Upper and Lower Continuous Fuzzy Multifunctions - İsmail Ibedou; Salah Abbas (Journal of New Theory, 2019)
In this paper, we introduce the concepts of upper and lower (α, β, θ, δ, \ell)-continuous fuzzy multifunctions. It is in order to unify several characterizations and properties of some kinds of modifications of fuzzy upper and fuzzy lower semi-continuous fuzzy multifunctions, and to deduce a generalized form of these concepts, namely upper and lower η η^{*}-continuous fuzzy multifunctions.